Mobile clouds : exploiting distributed resources in wireless, mobile and social networks - Fitzek, Frank H. P.; Katz, Marcos D. (John Wiley & Sons, 2014)
"Mobile Clouds: Exploiting Distributed Resources in Wireless Networks introduces in detail one of the most exciting technologies created after the invention of mobile phones, that is the exploitation of local grids of wireless devices (e.g. mobile phones, portable computers). The book addresses the problem of sharing resources in wireless networks and introduces a great number of novel cases in practical scenarios. Resources to be shared include radio resources to concrete physical resources onboard of the wireless devices, all distributed in the network. In addition, the authors introduce several cooperative strategies and distributed resource-sharing concepts for future mobile cloud applications. The dynamics of the cloud are also discussed, including cloud establishment, termination and updating. Mobile clouds benefit from a variety of enabling and emerging technologies, which are also presented and discussed in the book. Novel services and applications as well as possible business models are treated. One of the key challenges of wireless clouds is that wireless devices are energy limited (e.g., battery operated) and this aspect, as well as methods for enhancing energy efficiency are recurrent themes. Finally, the authors provide the reader with several hints of possible research directions, emerging trends and visions on this new appealing area of technology development"--